Haemoglobin mass in an anaemic female endurance runner before and after iron supplementation - Garvican, L. A.; Lobigs, L.; Telford, R. D.; Fallon, K.; Gore, C. J. (International Journal of Sports Physiology and Performance, 2011)
Haemoglobin mass in a female endurance athlete was measured via carbon monoxide rebreathing upon diagnosis of iron-deficiency anemia (haemoglobin concentration = 8.8 g/dL, ferritin = 9.9 ng/mL) and regularly during treatment thereafter. Haemoglobin mass increased by 49% in the 2 wk following an intramuscular iron injection and continued to increase with oral iron supplementation for 15 wk. The presented case illustrates that haemoglobin mass is readily responsive to iron supplementation in a severely iron-deficient anemic athlete and that changes can be tracked efficiently using the CO-rebreathing method.